Load Spectrum Compiling of Mining Loader Transmission System based on the Vehicle Test - Gao Huifeng; Lü Caiqin; Zhang Ke; Liu Sirong (Jixie chuandong)
With the development of coal mining industry,mining loader to become the largest demand for acquisition equipment. As China loader design mainly in the traditional design methods,the lack of systematic design. In the design stage,in order to determine its service life,it needs to carry on indoor bench fatigue test,so the compilation of load spectrum becomes more and more important. Taking the transmission system of mining loader as research object,a real vehicle road test is carried out according to typical designed condition. The signals eliminates and outliers eliminating for the acquisition of load signals is carried out. It has a statistical counting for the acquisition of load signals by using rain-flow counting method. Then it makes a load data extrapolation and weaves into an 8 program load spectrum,therefore,it can provide a basis for the design of mining loader in the future.